Studi Literatur : Penggunaan Media Kartu Domino Braille Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Sari, Yofita; Hadi, Waluyo; Handayani, Puji Tri (Universitas Muhammadiyah Magelang, 2024)
Mathematics learning at elementary school level is an important stage in forming an understanding of fundamental mathematical concepts. In the era of inclusive education, it is important to explore various learning media that can improve students' understanding, including students with special needs. One media that is attracting attention is Braille Domino Cards, which not only can help students with visual impairments, but also have the potential to improve mathematical understanding for all students. The aim of this research is to analyze the effect of using Braille Domino Card media on mathematics learning outcomes of elementary school students through a literature review. The method used is literature study. Literature study is described as a type of research that does not require researchers to make direct observations in the field. As a result of research from researchers, data was obtained relating to the application of domino card media to elementary school students' mathematics learning outcomes. Domino card media is defined as one of the game media in mathematics learning which can be used to provide practice questions to students. It can be concluded that this media makes a positive contribution to student learning outcomes. The use of Braille Domino Cards helps blind students improve their numeracy skills, especially in addition and reduction.